An overview of service quality towards guest’s satisfaction in hospitality industry / Aida Khalida Mohamed Idris ... [et al.] - Mohamed Idris, Aida Khalida; Mohd. Pakri, Nur Adnin; Hashim, Norliana; Nik Mohd Nor, Nik Mohd Shahril; Faat, Farhan (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
Sustainable development of hospitality industry in Malaysia has led numerous numbers of hotels, motels and other lodging accommodation to increase rapidly. It occurs due to the increment number of international and domestic tourist boarding in Malaysia. Owing to that, it is important for lodging provider to offer a good service quality because it will lead the guests feeling pleasant and satisfied during their stay. In return, it will increase the loyalty and high tendency of tourist to revisit or recommend to their friends. Researches have shown that service quality plays important elements in determining guest’s satisfaction. Guests are considered satisfied when they have the positive feeling throughout the process of evaluating the expectation and what they actually get. Due to the guest satisfaction mostly depended on the level of service quality and on how they are being treated during their stay at the lodging, it is crucial to search for a missing value in service quality towards guest’s satisfaction. Aforementioned by previous researchers shows that numerous issues have been raised pertaining of primary dimension and sub dimension in service quality when measuring satisfaction in several industries as many theories, measurements and models has been deformed recently. Therefore, this paper is to discuss the sub dimension for service quality towards guest’s satisfaction in Seberang Perai hotels.